EKSPLORASI KEARIFAN LOKAL USAHATANI TEMBAKAU SRINTHIL DI LERENG GUNUNG SUMBING - Agus Ganjar Runtiko; F. Trisakti Haryadi; Roso Witjaksono (Jurnal Kawistara, 2018)
Srinthil is the name of the high quality tobacco commodity in Temanggung District. The quality of Srinthil tobacco is indicated by the higher price compared to other tobacco. Nevertheless, the emergence of Srinthil tobacco is unpredictable. Tobacco farmers believe that the emergence of Srinthil is influenced by at least four factors; siti (land), wiji (seeds), wanci (time), and wahyu (luck). The four factors considered influencing the emergence of Srinthil tobacco are sought by farmers. Tobacco farmer’s effort to produce Srinthil resulting a variety of local wisdom. This study aims to describe the local wisdom constructed, believed, and practiced traditionally by tobacco farmers on the slopes of Mount Sumbing, Temanggung District. The method used in this study is qualitative with the case study approach, which focuses on the local wisdom of Srinthil tobacco farming. The study was conducted in Legoksari Village, Tlogomulyo sub-District in July-September 2017. Data collection was carried out by conducting in- depth interviews and focus group discussions on 15 farmers, as well as five traditional leaders and village officials, participatory observation, and secondary data searches. The results showed that the local wisdom of tobacco farming consisted of three main categories: traditional rituals, house design, and work ethic. Aside from being an effort to search for Srinthil, the local wisdom of tobacco farming also serves as a medium for intergenerational value transmission, means of prayer to God, preservation of nature/environment, and maintenance of social cohesion.